Suggested languages for you:

Americas

Europe

Q. 1

Expert-verifiedFound in: Page 870

Book edition
6th

Author(s)
Sullivan

Pages
1200 pages

ISBN
9780321795465

Quadratic equation is:

$3{x}^{2}-2x=-1$

We can rewrite the equation as:

$3{x}^{2}-2x+1=0$

By comparing $3{x}^{2}-2x+1=0$, with standard quadratic equation: $a{x}^{2}+bx+c=0$.

We get,

$a=3\phantom{\rule{0ex}{0ex}}b=-2\phantom{\rule{0ex}{0ex}}c=1$Substitute these values in the formula and solve.

$x=\frac{-(-2)\pm \sqrt{{(-2)}^{2}-4\left(3\right)\left(1\right)}}{2\left(1\right)}\phantom{\rule{0ex}{0ex}}x=\frac{2\pm \sqrt{4-12}}{2}\phantom{\rule{0ex}{0ex}}x=\frac{2\pm \sqrt{-8}}{2}\phantom{\rule{0ex}{0ex}}x=\frac{2\pm \sqrt{8{i}^{2}}}{2}\phantom{\rule{0ex}{0ex}}x=\frac{2\pm i2\sqrt{2}}{2}\phantom{\rule{0ex}{0ex}}x=\frac{2(1\pm i\sqrt{2})}{2}\phantom{\rule{0ex}{0ex}}x=1\pm i\sqrt{2}$

94% of StudySmarter users get better grades.

Sign up for free